Change Management and its Role in Enhancing Teacher Competency Through Technology Integration - R, Abu Hasan Agus; Muslim, Bukhori (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine the integration of technology in education from the perspective of change management theory, with a particular focus on developing educator competencies at Islamic Senior High School (Madrasah Aliyah) Miftahul Ulum, located in Sumberanyar, Paiton, Probolinggo, East Java. Using a qualitative case study design, the study draws on desk reviews of school policy documents and training records, classroom observations of technology-supported learning activities, and semi-structured interviews with teachers, school leaders, and IT coordinators. The collected data were analyzed using thematic analysis, following stages of data reduction, data display, and conclusion drawing to identify patterns aligned with Lewin’s change management framework. The findings reveal that adequate preparation (Unfreeze) through structured training and awareness-building significantly reduces resistance to technology adoption. During the implementation phase (Change), teachers demonstrate improved competencies in digital assessment, learning management systems, and collaborative tools. Sustaining change (Refreeze) requires continuous professional development, consistent leadership support, and peer collaboration to ensure long-term integration. The study contributes both theoretically and practically by offering a contextualized application of Lewin’s change management model within an Islamic secondary school setting and by providing evidence-based strategies for strengthening educator digital competence. Practically, the research guides schools in designing structured training programs and cultivating collaborative cultures to enhance effective and sustainable technology integration. Theoretically, it enriches the discourse on change management in educational technology by illustrating how classical change models operate in faith-based school environments.